Trouble with the curve: the 90–9-1 rule to measure volitional participation inequalities among Royal Canadian Mounted Police cadets during training - Teckchandani, Taylor A.; Shields, Robyn E.; Andrews, Katie L.; Maguire, Kirby Q.; Jamshidi, Laleh; Nisbet, Jolan; Afifi, Tracie O.; Lix, Lisa M.; Stewart, Sherry H.; Sauer-Zavala, Shannon; Krakauer, Rachel L.; Neary, J. Patrick; et al. (Frontiers in Psychiatry, 2024)
The Royal Canadian Mounted Police (RCMP) Study includes longitudinal multimodal assessments of RCMP cadets from pre-training (i.e., starting the Cadet Training Program [CTP]) to five years after deployment (Carleton et al., 2022). The data affords an investigation of the multidimensionality of volitional participation, and the impact of participation inequalities by classifying cadets using the 90-9-1 rule. Participants were asked to complete a full assessment prior to their training at CTP, as well as short daily surveys throughout their training. Participation frequency was described using a process where participants were rank ordered by the number of daily surveys completed and classified into one of three categories. Full assessment surveys completed prior to their training at CTP included screening tools for generalized anxiety disorder (GAD), major depressive disorder (MDD), posttraumatic stress disorder (PTSD), alcohol use disorder (AUD), and panic disorder (PD). The Kruskal-Wallis H test assessed differences in participation rates between mental health disorder symptom screening groups for each measure at pre-training. Spearman's Rho was used to describe associations amongst mental health disorder symptoms and the number of daily surveys completed during CTP. There were 18557 daily survey records collected from 772 participants. The rank-ordering of cadets by the number of daily surveys completed produced three categories in line with the 90-9-1 rule: Superusers who were the top 1% of cadets (n=8) and produced 6.4% of all recordings; Contributors who were the next 9% of cadets (n=68) and produced 49.2% of the recordings; and Lurkers who were the next 90% of cadets (n=695) and produced 44.4% of daily survey recordings. Lurkers had the largest proportion of positive screens for self-reported mental health disorders at pre-training. The creation of highly individualized, population-based mental health injury programs has been limited by an incomplete understanding of the causal relationships between protective factors and mental health. The current results suggest persons with mental health challenges may be less likely to engage in some forms of proactive mental health training. The current results also provide useful information about participation, adherence, and engagement that can be used to inform evidence-based paradigm shifts in health-related data collection.